2017
DOI: 10.13005/bbra/2483
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Musculoskeletal Disorders among Taxi Industry Workers in Jeddah, Saudi Arabia

Abstract: Professional driving is associated with high rates of occupational musculoskeletal disorders (OMSDs). The objective of this study was to assess the prevalence of OMSDs among drivers and office workers of taxi industry in Jeddah city. A detailed custom-made questionnaire was used that included socio-demographic and occupational characteristics of subjects together with OMSDs prevalence rates. In this research, 173 subjects participated of which 70.5% were drivers and 29.5% were office workers. Standard Nordic Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
5
10
1
Order By: Relevance
“…According to this study’s results, it was also possible to verify that the most common musculoskeletal pain area was the low back, followed by the neck. This result coincides with most of the existing studies conducted in Saudi Arabia that were related to musculoskeletal disorders [ 3 , 30 , 31 , 34 ]. However, this result was slightly different from the results found by Sirajudeen et al [ 29 ] since they observed that the neck was the most common pain area, followed by the low back.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to this study’s results, it was also possible to verify that the most common musculoskeletal pain area was the low back, followed by the neck. This result coincides with most of the existing studies conducted in Saudi Arabia that were related to musculoskeletal disorders [ 3 , 30 , 31 , 34 ]. However, this result was slightly different from the results found by Sirajudeen et al [ 29 ] since they observed that the neck was the most common pain area, followed by the low back.…”
Section: Discussionsupporting
confidence: 91%
“…However, our study´s LBP point prevalence was considerably lower than the 53.2% to 79.17% found by Awaji [ 14 ] in a review made using seven cross-sectional studies conducted in Saudi Arabia. In other recent studies also undertaken in Saudi Arabia among specific professional groups, the point prevalence of LBP found was 80% in nurses [ 10 ], 57.3% in male high school teachers [ 13 ], 55% among faculty members [ 29 ], 40.5% in medical students [ 30 ], 51.6% in taxi drivers, 31.4% in office workers [ 31 ], and 21.2% among health sciences students [ 32 ]. Hence, in most of these cases, the point prevalence was higher than in our study, which could be related to the burden of work, type of professional or academic activity carried out by each group, and poor posture at work [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most older taxi drivers drove taxis with a frequency of 6> 10 times (62.8%) in a day, with the average driving within a week being 30.0 ± 13.1 times and 53.0% stating that they did not take a break within a week. This statement supports a previous study that 64.0% of taxi drivers in China who do not take a break within a month (Wang et al, 2017), and 80.3% do not take a break within a week (Ahmad et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The result stated, 45.4% waiting time to obtain a passenger in a day is 2 to 3 hours, and 57.6% did not nap to obtain a passenger. Several previous studies have also shown similarities with the study results (Abledu et al, 2014;Ahmad et al, 2017;Wang et al, 2017;. The majority (91.4%) of older taxi drivers drive more than 251 km of driving distance in a week.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation